Advances in Natural Language Processing 8th International Conference on NLP, JapTAL 2012, Kanazawa, Japan, October 22-24, 2012. Proceedings - Isahara, Hitoshi; Kanzaki, Kyoko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 8th International Conference on Advances in Natural Language Processing, JapTAL 2012, Kanazawa, Japan, in October 2012. The 27 revised full papers and 5 revised short papers presented were carefully reviewed and selected from 42 submissions. The papers are organized in topical sections on machine translation, multilingual issues, resouces, semantic analysis, sentiment analysis, as well as speech and generation.
The Impact of Crowdsourcing Post-editing with the Collaborative Translation Framework -- Translation of Quantifiers in Japanese-Chinese Machine Translation -- Toward Practical Use of Machine Translation -- Phrase-Level Pattern-Based Machine Translation Based on Analogical Mapping Method -- Parallel Texts Extraction from Multimodal Comparable Corpora -- A Reliable Communication System to Maximize the Communication Quality -- DAnIEL: Language Independent Character-Based News Surveillance -- OOV Term Translation, Context Information and Definition Extraction Based on OOV Term Type Prediction -- Exploiting a Web-Based Encyclopedia as a Knowledge Base for the Extraction of Multilingual Terminology -- Segmenting Long Sentence Pairs to Improve Word Alignment in English-Hindi Parallel Corpora -- Shallow Syntactic Preprocessing for Statistical Machine Translation -- Linguistic Rules Based Approach for Automatic Restoration of Accents on French Texts -- Word Clustering for Persian Statistical Parsing -- Building a Lexically and Semantically-Rich Resource for Paraphrase Processing -- Tagset Conversion with Decision Trees -- Fitting a Round Peg in a Square Hole: Japanese Resource Grammar in GF -- Arabic Language Analyzer with Lemma Extraction and Rich Tagset -- Tracking Researcher Mobility on the Web Using Snippet Semantic Analysis -- Semantic Role Labelling without Deep Syntactic Parsing -- Temporal Information Extraction with Cross-Language Projected Data -- Word Sense Disambiguation Based on Example Sentences in Dictionary and Automatically Acquired from Parallel Corpus -- A Study on Hierarchical Table of Indexes for Multi-documents -- Finding Good Initial Cluster Center by Using Maximum Average Distance -- Applying a Burst Model to Detect Bursty Topics in a Topic Model -- UDRST: A Novel System for Unlabeled Discourse Parsing in the RST Framework -- Long-Term Goal Discovery in the Twitter Posts through the Word-Pair LDA Model -- Finding Social Relationships by Extracting Polite Language in Micro-blog Exchanges -- Twitter Sentiment Analysis Based on Writing Style -- Extraction of User Opinions by Adjective-Context Co-clustering for Game Review Texts -- Automatic Phone Alignment: A Comparison between Speaker- Independent Models and Models Trained on the Corpus to Align -- A Story Generation System Based on Propp Theory: As a Mechanism in an Integrated Narrative Generation System -- Automatic Utterance Generation by Keeping Track of the Conversation$1 (Bs Focus within the Utterance Window.s
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Mathematical Logic and Formal Languages; Information Systems Applications (incl. Internet).; Database Management; Data Mining and Knowledge Discovery